Collaborative governance in food policy affairs: an examination of peatland damage mitigation strategies In Sungai Apit Regency, Indonesia - Albintani, Muchid; Susanto, Agus; Notatema Zebua, Ben Hansel; Wasillah, Asiah; Harirah, Zulfa; Ismandianto, Ismandianto (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
The degradation of peatlands attributable to anthropogenic activities, including the conversion of land for agricultural purposes and unsustainable land use practices, has culminated in a reduction of local food productivity and has adversely impacted food security in the Sungai Apit Subdistrict of Siak Regency, Indonesia. This research endeavor seeks to critically assess the efficacy of collaborative governance in the amelioration of peatland degradation and its ramifications on food policy. The methodological framework employed in this study is qualitative descriptive, utilizing data collection techniques that encompass comprehensive interviews, empirical field observations, and rigorous document analysis. The results indicate that institutional frameworks and leadership dynamics are pivotal dimensions that significantly affect the efficacy of collaborative efforts, notwithstanding the observed weakness in coordination among stakeholders. The predominance of governmental authority in decision making processes, coupled with a general lack of public awareness regarding the significance of peatland conservation, constitutes substantial barriers to progress. As a strategic intervention, the implementation of food diversification initiatives, such as the cultivation of hybrid coconuts, maize, and sweet potatoes, is advocated to mitigate reliance on rice and to enhance local food security. The study advocates for the fortification of participatory platforms, the enhancement of cross-sectoral coordination, along with community empowerment through educational programs and innovations in eco-technology. By adopting a more inclusive approach to collaborative governance, there exists a potential to foster sustainable food systems within regions characterized by vulnerable ecosystems, such as peatlands.